Growth hormone abuse and biological passport: Is mannan-binding lectin a complementary candidate? - Such-Sanmartin, G.; Bosch, J.; Segura, J.; Gutierrez-Gallego, R. (Clinical Journal of Sport Medicine, 2011)
Objective: In the detection of human growth hormone (GH) abuse, the approach based on altered GH-related biomarkers is also being considered with respect to its application within the context of a biological passport. As a potential biomarker, mannan-binding lectin (MBL), which is reported to respond to recombinant GH (rGH) administration, is evaluated here.